Case report: Aborted sudden cardiac death as a first presentation of severe mitral annulus disjunction—a case series and review of the literature - Apostolou, Fay; Ioannides, Marios; Mitsis, Andreas; Koutsofti, Constantina; Deltas, Constantinos; Avraamides, Panayiotis (Frontiers in Cardiovascular Medicine, 2023)
Mitral annulus disjunction (MAD) is defined as a systolic displacement between the ventricular myocardium and the posterior mitral annulus supporting the posterior mitral leaflet. This structural abnormality is associated with the loss of mechanical annular function manifested as an abnormal systolic excursion of the leaflet hinge point into the left atrium but with maintained electrical function, separating the left atrium and ventricle electrophysiologically. The mitro-aortic fibrous continuity limits MAD anteriorly, between the aortic cusps and the anterior leaflet of the mitral valve. Consequently, MAD has been observed only at the insertion of the posterior leaflet. It can extend preferentially at the central posterior scallop. The first diagnostic modality aiding the diagnosis is transthoracic echocardiography (TTE), although in some cases adjunctive cardiac imaging modality might be suggested. MAD carries a strong association with malignant ventricular arrhythmogenesis and a profound predisposition for sudden cardiac death (SCD). In this context, a thorough investigation of this morphological and functional abnormality is vital in estimating the risk assessment and stratification for optimal management and elimination of the risk of the patient for SCD. Based on the current scientific data and literature, we will discuss the diagnosis, clinical implications, risk stratification, and therapeutic management of MAD.